Pre-service English Teacher Experience of Using Video-based Descriptive Text Writing During Teaching Practicum: A Narrative Analysis - Faisal, Danang Muhammad; Miftkah, Fauzi (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
This research aims to find pre-service teacher experience of implementing Video-based Descriptive text during teaching practicum. One insider participant was involved in this research to find his view and perception about the use of video. To process data from participants in the form of self-reflective journals, qualitative methods and thematic analysis are used. This study also presented several other findings, such as emotional and technical problems, social experience, and pedagogical experience. According to this study, when using video-based to teach descriptive writing, participants must put in extra effort, such as making the video interactive and engaging enough for students to watch. Furthermore, the use of video-based has been shown to provide participants with flexibility. One disadvantage of this method is that the teaching process in this way is quite ineffective.